STRATEGI KEPEMIMPINAN TRANSFORMASIONAL DALAM MENINGKATKAN PROFESIONALISME GURU DI SMK SWASTA BUDI UTOMO BINJAI - Melsa Karolina Br Purba; Hamidah Darma; Rabukit Damanik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe and analyze the implementation of transformational leadership practices by the principal in improving teacher professionalism at SMK Swasta Budi Utomo Binjai. Teacher professionalism serves as a key component in efforts to enhance the quality of education; therefore, the principal’s leadership plays a crucial role in determining the direction and quality of teachers’ performance. The research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, field observations, and document analysis. The research informants consisted of the principal, vice principal, and several teachers selected proportionally to represent the. The findings indicate that the principal implemented transformational leadership strategies through four main dimensions: (1) Idealized Influence, demonstrated by modeling exemplary behavior and decision-making; (2) Inspirational Motivation, shown through the communication of a clear vision and the encouragement of teachers’ work enthusiasm;(3) Intellectual Stimulation, by motivating teachers to think innovatively and critically in the learning process; and (4) Individualized Consideration, by providing attention and support for each teacher’s needs and professional development. The implementation of these strategies has proven effective in enhancing teachers’ commitment, responsibility, and performance quality. In conclusion, the principal’s transformational leadership plays a significant role in fostering and improving teacher professionalism, which ultimately contributes positively to the overall quality of education in the school. Based on the findings, it is recommended that the principal continue to strengthen participatory leadership practices and focus on developing human resource potential within the school environment.